Estimation of aerodynamic parameters of IIUM hybrid airship - Andan, Amelda Dianne; Asrar, Waqar; Omar, Ashraf Ali (2011)
The aerodynamic parameters of a preliminary IIUM low speed winged-hull airship design is investigated. The objective is to study the aerodynamic parameters of the wingedhull airship and to find the necessities of attaching wings to the existing IIUM low speed airship. The research methodology involved the use of numerical simulation and laboratory testing to study fluid flow over a half scaled winged-hull airship model. The aerodynamic parameters of the design are first computed by computational fluid dynamics. The research work continues in laboratory testing with wind tunnel and six component balances as the main tool. The total forces and moment coefficients are then collected at a selected range of angles. The results obtained were as predicted, lift forces increases tremendously with reasonable increase in drag. The longitudinal and directional stabilities were found to be statically stable, however, both airship model have poor rolling stability. Nonetheless, the overall study shows that attaching wings to the existing IIUM low speed airship is feasible.